Development of gamification-based e-module on global warming material for grade X - Novita Resti; Kusnadi Kusnadi; Amprasto Amprasto (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Although electronic modules offer interactivity, the integration of gamification remains limited, particularly for topics such as global warming in high school biology. This gap highlights the need for teaching materials that align with the demands of the digital era and the characteristics of modern learners. This study aims to develop a gamification-based e-module on global warming, determine the feasibility of the developed e-module, and assess student responses. This research is of the Research and Development (R&D) type using the 4D model, limited to the development stage. The instruments used in this study include interview sheets and environmental literacy questions in the define stage, the e-module design blueprint in the design stage, content feasibility validation sheets, graphic design and language validation sheets, as well as student response questionnaires in the development stage. The results of this research are as follows: (1) the feasibility of the gamification-based e-module in terms of content has a score of 85.49, categorized as "very feasible," (2) the feasibility in terms of graphic design has a score of 91.16, categorized as "very feasible," (3) the feasibility in terms of language has a score of 87.27, categorized as "very feasible," (4) the average student response score is 91.11, with 89% of students giving a positive response to the e-module, and (5) the gamification-based e-module on global warming is highly feasible to be used in the learning process. This study has both theoretical and practical implications. Theoretically, the gamification-based e-module opens opportunities for the development of more interactive learning materials that can enhance environmental literacy and learning motivation. Practically, this e-module serves as an engaging alternative in science education, particularly in biology, and can be further developed by teachers for various subjects and educational levels.Abstrak. Meskipun modul elektronik menawarkan interaktivitas, integrasi gamifikasi masih terbatas, terutama untuk topik seperti pemanasan global dalam biologi SMA. Kesenjangan ini menyoroti kebutuhan akan bahan ajar yang sesuai dengan tuntutan era digital dan karakteristik pembelajar modern. Penelitian ini bertujuan untuk mengembangkan e-module berbasis gamifikasi pada materi pemanasan global, mengetahui kelayakan dari e-module yang dikembangkan dan respon peserta didik. Jenis penelitian ini adalah Research and Development (R&D) dengan menggunakan model 4D yang dibatasi hanya sampai pada tahap development. Instrumen pada penelitian ini adalah lembar wawancara, lembar validasi kelayakan isi materi, kegrafikan dan bahasa serta angket respon. Hasil penelitian yaitu; (1) kelayakan e-module berbasis gamifikasi pada aspek kelayakan isi adalah 85,49 dengan kategori “sangat layak”, (2) kelayakan pada aspek kegrafikan mendapatkan nilai 91,16 dengan kategori “sangat layak”, (3) kelayakan pada aspek bahasa sebesar 87,27 dengan kategori “sangat layak”, (4) nilai rata-rata respon peserta didik yaitu sebesar 91,11 dengan 89% peserta didik memberikan respon positif terhadap e-module (5) e-module berbasis gamifikasi pada materi pemanasan global sangat layak digunakan dalam proses pembelajaran. Penelitian ini memiliki implikasi baik secara teoritis maupun praktis. Secara teoritis, e-module berbasis gamifikasi membuka peluang untuk pengembangan bahan ajar yang lebih interaktif yang dapat meningkatkan literasi lingkungan dan motivasi belajar peserta didik. Secara praktis, e-module ini berfungsi sebagai alternatif menarik dalam pendidikan sains, khususnya biologi, dan dapat dikembangkan lebih lanjut oleh guru untuk berbagai mata pelajaran dan jenjang pendidikan.